A theological perspective on abortion - R T H Dolamo (Acta Theologica)
The ongoing debate on abortion, the world over, cannot be brought to any finality. Reader's Digest Oxford Complete Wordfinder defines abortion as "the expulsion of a foetus (naturally or esp. by medical induction) form the womb before it is able to survive independently, esp. in the first 28 weeks of a human pregnancy".